2021
DOI: 10.1016/j.redox.2021.102088
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-ketoglutarate ameliorates pressure overload-induced chronic cardiac dysfunction in mice

Abstract: Increasing evidence indicates the involvement of myocardial oxidative injury and mitochondrial dysfunction in the pathophysiology of heart failure (HF). Alpha-ketoglutarate (AKG) is an intermediate metabolite of the tricarboxylic acid (TCA) cycle that participates in different cellular metabolic and regulatory pathways. The circulating concentration of AKG was found to decrease with ageing and is elevated after acute exercise and resistance exercise and in HF. Recent studies in experimental models have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 57 publications
(104 reference statements)
2
48
0
Order By: Relevance
“…α -KG supplementation has been shown to improve cardiac contractile dysfunction in transverse aortic constriction (TAC) mice by attenuating pressure overload-induced cardiac hypertrophy and fibrosis. Further, α -KG exerts cardioprotective effects in TAC-induced failing myocardium by: 1) reducing ROS production and oxidative stress, 2) inhibiting cardiomyocyte apoptosis, 3) promoting autophagy and mitophagy, and 4) improving mitochondrial membrane potential 64,65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α -KG supplementation has been shown to improve cardiac contractile dysfunction in transverse aortic constriction (TAC) mice by attenuating pressure overload-induced cardiac hypertrophy and fibrosis. Further, α -KG exerts cardioprotective effects in TAC-induced failing myocardium by: 1) reducing ROS production and oxidative stress, 2) inhibiting cardiomyocyte apoptosis, 3) promoting autophagy and mitophagy, and 4) improving mitochondrial membrane potential 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we also identified tricarboxylic acid (TCA) cycle (citric acid cycle) as one of the top common dysregulated metabolic pathways in RV of MCT and Su/Hx rats (Figure 8). a-ketoglutarate (a-KG), as a crucial intermediate metabolite of TCA cycle, regulates ATP production and mitochondrial energy homeostasis [62][63][64] . Interestingly we found a significant decrease in a-KG in both MCT and Su/Hx rats (Figure 4C).…”
Section: Metabolic Reprogramming In Rv Of Decompensated Ph-rvf: Role ...mentioning
confidence: 99%
“…A very recent study has found that external supplementation of alpha-ketoglutarate (AKG), an intermediate metabolite of the tricarboxylic acid cycle, effectively suppressed transverse aortic constriction (TAC)-induced cardiac hypertrophy and improved heart function ( 82 ). The cardio-protective roles of AKG may be achieved by promoting mitophagy, which helped to remove damaged mitochondria and reduce ROS production ( 82 ). Allyl Methyl Sulfide (AMS) intervention also exerted protective effects on TAC-induced cardiac hypertrophy.…”
Section: Potential Therapeutic Approaches Targeting Mitochondria To Prevent or Reverse Cardiac Hypertrophymentioning
confidence: 99%
“…GPR99 KO mice show a significant increase in cardiac hypertrophy decrease in cardiac shortening and ejection fraction following transverse aortic constriction [ 358 , 359 ]. Neonatal rat cardiomyocytes overexpressing OXGR1 show reduced phenylephrine-induced cardiomyocyte hypertrophy [ 360 ].…”
Section: Tca Cycle Metaboltesmentioning
confidence: 99%